DESIGNING A COUNTERFEIT-PRODUCT-CHECK APPLICATION USING ANDROID BASED BARCODE SCANNER IN COSMETICS PRODUCTS - Delima Sitanggang; Juan; Greace; Evta Indra (Sean Institute, 2021)
In this day and age, all information can be searched and obtained from technological developments. The more users of technology such as smartphones/androids among the wider community, the more information that can be obtained. Currently, there are many cases of violations of cosmetic circulation in Indonesia. Such as the circulation of products without a registration code from the BPOM (Food and Drug Supervisory Agency) which is faked by irresponsible parties. Of the many cases of cosmetic violations, along with changes in people's lifestyles such as changes in consumption patterns (users). At this time, public knowledge is still minimal about choosing and using safe cosmetic products. The application of cosmetic safety check applications is an option for consumers because with this application they can check for themselves whether the products to be used are genuine or fake. The method used in this study is to use qualitative methods and the waterfall method. This application is expected to help the public before buying a cosmetic product, simply by checking the barcode and scanning using a smartphone/android, consumers can quickly find out whether a cosmetic product is genuine or not before using it..